Synthesis and Characterization of Silver Nanoparticles Using Bioreductant Andong Leaf Extract (Cordyline fruticosa (L) A. Chev.) - Mayang Sulistiorini; Gusrizal Gusrizal; Ajuk Sapar (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2024)
Silver nanoparticles are known to play a crucial role in various fields, prompting researchers to undertake synthesis and modification to obtain nanoscale particles. Silver nanoparticles were synthesized using a green synthesis-based chemical method with an extract from Cordyline fruticosa (L.) A. Chev. This study aims to determine the optimum conditions, including pH parameters, reaction time, and concentration, and assess the silver nanoparticles’ stability and characteristics. The research findings revealed that the optimal conditions for synthesizing silver nanoparticles were an extract pH of 11, a reaction time of 60 minutes, a AgNO3 concentration of 1.5 x 10-4 M, and an extract concentration of 0.008%. Characterization showed that silver nanoparticles were spherical, ranging from 5 to 20 nm and had an average hydrodynamic size distribution of 100.8 nm. In conclusion, leaf extract of Cordyline fruticosa (L.) A. Chev. can be utilized as a bioreductant and stabilizing agent, as indicated by stability test results, which showed considerable stability over a storage period of three months.